An Enhanced Vehicle-to-Vehicle Wireless Power Transfer System for Electric Vehicle Applications Using a Reconfigurable Coil Approach - Venkatesan Ramakrishnan; Dominic Savio A; Mohammad Shorfuzzaman; Waleed Mohammed Abdelfattah (IEEE Access)
The growth of Electric Vehicle (EV) technologies necessitates adequate charging infrastructure and energy storage systems for reliable operation. Conversely, vehicle-to-grid, vehicle-to-home, and vehicle-to-vehicle (V2V) technologies are being researched to enhance EV usage. V2V technology can assist EV users with convenient power sharing during emergencies. However, the conventional plug-in approach limits safety and human intervention aspects. Recent advancements in wireless power transfer (WPT) offer both convenience and reliable power exchange, making them the most suitable approach for V2V technology. WPT is a loosely coupled system, and the air gap increases leakage inductance, which weakens the coupling factor (K) and affects power transfer efficiency (PTE). In this article, the enhancement of the coupling factor is achieved by employing a reconfigurable coil between the Transmitter (Tx) coil and the Receiver (Rx) coil. This reconfigurable coil functions as a resonator, enhancing the flux generated by the Tx coil and improving PTE. Furthermore, the proposed system facilitates bidirectional power flow between two EVs. The phase shift control technique regulates the power flow between the two EVs. Improved efficient WPT conserves energy and reduces the reliance on energy storage devices. The proposed WPT system is validated with a 500W prototype model and realized efficiency of 92.6 % in aligned condition and 86.6% at 40% lateral misaligned condition.